2017
DOI: 10.1016/s0924-977x(17)30130-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone are influenced by childhood adversity during negative emotional processing in addiction recovery

Abstract: Naltrexone is an opioid receptor antagonist used in the management of alcohol dependence. Although the endogenous opioid system has been implicated in emotion regulation, the effects of mu-opioid receptor blockade on brain systems underlying negative emotional processing are not clear in addiction. Individuals meeting criteria for alcohol dependence alone (n = 18, alcohol) and in combination with cocaine and/or opioid dependence (n = 21, alcohol/drugs) and healthy individuals without a history of alcohol or dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The few naltrexone studies that have examined functional connectivity vary in analysis parameters, populations of interest, and study designs. These studies have shown that naltrexone modulates connectivity between ACC and hippocampus as a function of childhood adversity during an emotional priming task among alcohol-dependent individuals (Savulich et al, 2017), and that naltrexone improves local network efficiency in alcohol dependent individuals, reaching that of healthy controls (Morris et al, 2018). Most notably, in a study of methamphetamine users, naltrexone decreased connectivity between precuneus and sensorimontor regions and increased connectivity between dorsal striatum and precuneus with frontal regions (Courtney et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The few naltrexone studies that have examined functional connectivity vary in analysis parameters, populations of interest, and study designs. These studies have shown that naltrexone modulates connectivity between ACC and hippocampus as a function of childhood adversity during an emotional priming task among alcohol-dependent individuals (Savulich et al, 2017), and that naltrexone improves local network efficiency in alcohol dependent individuals, reaching that of healthy controls (Morris et al, 2018). Most notably, in a study of methamphetamine users, naltrexone decreased connectivity between precuneus and sensorimontor regions and increased connectivity between dorsal striatum and precuneus with frontal regions (Courtney et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In-vivo microdialysis studies have linked receptor tone with drug reinforcement, where greater endogenous dopamine activity is associated with more adverse effects of cocaine-a dopamine reuptake inhibitor. 30 Greater activity in the medial pre-frontal cortex was found when responding to aversive images in people with a history of childhood adversity after receiving naltrexone, 31 although this study was confined to those with histories of drug and/or alcohol abuse. The authors suggest this may reflect greater effort to exert emotion regulation.…”
Section: Introductionmentioning
confidence: 85%
“…Prior research has linked childhood trauma to altered neural responses to naltrexone, potentially via existing differences in endogenous opioids. 31 Preclinical research has also reported that maternal separation results in hyposensitive endogenous opioid functioning, which is suggested as responsible for the heightened sensitivity to the rewarding effects of opioid drugs. 20 A hyposensitive endogenous opioid system could T A B L E 2 Plasma morphine and physiological outcomes (Ms and SDs) therefore potentially underlie the increased pleasurable effects and reduced aversive effects of morphine in the trauma group in the current study.…”
Section: (A) (C) (D)mentioning
confidence: 99%
“…Clinical evidence also suggests that MOR blockade with naltrexone is effective in some impulse control disorders (Kim et al, 2001;Grant, 2005;Lahti et al, 2010;Grant et al, 2014), promotes abstinence in substance addiction populations (Krystal et al, 2001;Srisurapanont & Jarusuraisin, 2005;Grassi et al, 2007), possibly through the promotion of impulse control (Sanchez-Roige et al, 2015). There is evidence that naltrexone can also ameliorate neural disturbances in addiction (Savulich et al, 2017;Morris et al, 2018), including those related to impulsive choice (Boettiger et al, 2009), pointing to its potential efficacy as a neuromodulator of impulse control. Therefore, evidence of disturbances to prefrontal endogenous opioid functioning, together with the clinical efficacy of naltrexone in treating impulse control and addiction disorders, suggests that this system may be a viable target for relapse prevention, where there are deficits related to impulsivity.…”
Section: Introductionmentioning
confidence: 99%